.NET 4.5 Parallel Extensions cookbook - Freeman, Bryan (Packt Publishing, 2013)
This book contains practical recipes on everything you will need to create task-based parallel programs using C♯, .NET 4.5, and Visual Studio. The book is packed with illustrated code examples to create scalable programs. This book is intended to help experienced C♯ developers write applications that leverage the power of modern multicore processors. It provides the necessary knowledge for an experienced C♯ developer to work with .NET parallelism APIs. Previous experience of writing multithreaded applications is not necessary.